Aresztowanie i śledztwo przeciwko adwokatowi Andrzejowi Jochelsonowi jako przykład represji komunistycznych wobec adwokatury wrocławskiej - Pluta, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Repressions of communist security services against Wrocław lawyers have not been researched by law historians so far. Andrzej Jochelson is one of the leading figures of the Wrocław Bar, who was subjected to a hard Stalinist investigation. The main reason of Jochelson’s arrest was his collaboration with the Apostolic Administration Curia in Wrocław as well as his political activities in the Labour Party. The main objective of the investigation was to force the lawyer to incriminate Father Karol Milik, the apostolic administrator. Despite their ruthless interrogation methods the security services were unable to break Jochelson. Throughout the investigation the lawyer behaved with of dignity.
Keywords: adwokatura; donosy agentów; Milik, Karol; Kościół; śledztwo; Wojewódzki Urząd Bezpieczeństwa Publicznego; Wrocław